Artificial intelligence in healthcare text processing: a review applied to named entity recognition - de Almeida, Samuel Santana; Silva Fontes, Raphael; Pareja Credidio Freire Alves, Luca; Júnior, Methanias Colaço; José Pinheiro Caldeira Silva, Gleyson; Ramalho Cortez, Lyane; de Morais, Antonio Higor Freire; Medeiros Machado, Guilherme; Gonçalo Oliveira, Hugo; Cunha-Oliveira, Aliete; dos Santos, João Paulo Queiroz; de Medeiros Valentim, Ricardo Alexsandro (Frontiers in Artificial Intelligence, 2025)
ContextTraditional methods such as rule-based systems, word embeddings (e.g. Word2Vec, GloVe) and sequence tagging models such as CRFs and HMMs have difficulty capturing the complex and nuanced context of medical texts, leading to low precision and inflexibility. These methods also struggle with the inherent variability of medical language and often require large and difficult-to-obtain labeled datasets.ObjectiveWe examine the growing importance of Named Entity Recognition (NER) in the analysis of healthcare texts. NER, a fundamental technique in Natural Language Processing (NLP), automatically identifies and categorizes named entities in the text, such as names of people and organizations, in medical texts, medical conditions and drug names. This facilitates better information retrieval, personalized medicine approaches and clinical decision support systems.MethodsA systematic mapping was carried out that focused on advanced language models, specifically transformation-based models such as BERT. These models are known for capturing complex semantic dependencies and linguistic nuances, which are crucial for accurate processing of medical texts. Transformation architectures, unlike traditional techniques such as CNNs and RNNs, are better suited to dealing with the contextual and semantic nature of medical texts due to their ability to manage long sequences and the need for high precision.ResultsThe results indicate that transformation-based models, in particular BERT and its specialized variants (e.g. ClinicalBERT), consistently demonstrate high performance on NER tasks, with F1 scores often exceeding 97%, outperforming traditional and hybrid methods. When examining the geographical distribution of contributions, the research identifies a significant contribution from China, followed by the United States. These findings have crucial implications for the integration of NER technologies into the Brazilian National Health System (SUS).ConclusionThis systematic review contributes to the advancement of NER in health texts by evaluating methods, showing results and highlighting the wider implications for the field. The article is systematically structured into the following sections: Methodology, Bibliometric analysis, Results and discussion, Threats to validity, Future work and Conclusion. This systematic organization provides a comprehensive review of the research, its impact and future directions, highlighting the importance of keeping up to date with advances in the field to increase the relevance of NER applications in healthcare.